1948
DOI: 10.1037/h0057264
|View full text |Cite
|
Sign up to set email alerts
|

Methods for determining patterns of leadership behavior in relation to organization structure and objectives.

Abstract: has undertaken a series of studies under the title "Leadership in a Democracy " One phase of these studies includes an investigation of executive positions and organization structures in industrial, military, educational, and civilian governmental organizations. The aims of this research are to develop improved methodology for studying leadership, to establish criteria for judging it, and to prepare information and techniques which may be useful m selecting and training persons who may occupy leadership positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

1976
1976
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 0 publications
0
28
0
1
Order By: Relevance
“…An unwillingness of leadership scholars, however, to heed Stogdill and Shartle's (1948) admonition to test this assumption risks continuing to take leadership research down a dead-end street or, perhaps more accurately, a circular drive. If managers and leaders are not identical and, if most leadership research continues to use bmanagersQ and their bsubordinatesQ as subjects, then what is revealed about managers may have nothing to say about bleadersQ and their bfollowers.Q Taken to the extreme, this one flaw could move leadership research back to square one.…”
Section: The Past Lives In the Presentmentioning
confidence: 95%
See 1 more Smart Citation
“…An unwillingness of leadership scholars, however, to heed Stogdill and Shartle's (1948) admonition to test this assumption risks continuing to take leadership research down a dead-end street or, perhaps more accurately, a circular drive. If managers and leaders are not identical and, if most leadership research continues to use bmanagersQ and their bsubordinatesQ as subjects, then what is revealed about managers may have nothing to say about bleadersQ and their bfollowers.Q Taken to the extreme, this one flaw could move leadership research back to square one.…”
Section: The Past Lives In the Presentmentioning
confidence: 95%
“….exercised influenceQ (p.152) was, thus, based on an admitted assumption. As expressed by Stogdill and Shartle (1948), Morris and Seeman's OSU colleagues, bIt is assumed that leadership in some form exists in top administrative positions, as well as at other levels in the organization [and, thus,] it is proper and feasible to make a study of leadership in places where leadership would appear to exist and that if a person occupies a leadership position he is a fit subject for studyQ (p. 287). Whereas Stogdill and Shartle then proceeded to proclaim that, bThe question as to whether leaders or executives are being studied appears to be a problem at the verbal level only,Q they do acknowledge that bthe soundness of these assumptionsQ must be tested (p. 287).…”
Section: Osu Leadership Studiesmentioning
confidence: 99%
“…Roff found the greatest discrepancy on the interpersonal level, where superiors were rated lower than their subordinates. Stogdill and Shartle (1948) did a study similar to Roff's. Twenty-four officers of the Naval Command Staff rated the persons with whom they worked and themselves on an RAD index (responsibility, authority, and delegation).…”
Section: Role Expectationmentioning
confidence: 98%
“…Although one criterion pertains more to task accomplishment and the other to individual need satisfaction, both are highly correlated with the successful interpersonal relationships between group and group member and between leader and group members. Stogdill and Shartle (1948) indicated in their study that, because research must be conducted within the interpersonal situation from which leadership evolves, concentration must be used primarily to find the relationships between jobs that leaders do, since &dquo;leadership is the process of getting things done.&dquo; From this, selection criteria can be developed. Distinctions among various studies cannot be easily drawn.…”
Section: Group Factorsmentioning
confidence: 99%
“…Bedeian also explains that these researchers argued that they were severely limiting the generalizability of their results by using managers as surrogates for leaders. Stogdill and Shartle (1948), two other Ohio State researchers, argued that they assumed leadership in some form exists at top organizational levels as well as lower organizational levels. Therefore, it was proper and feasible to examine leadership in places where leadership would appear to exist, and a person occupying such a position would be appropriate to examine.…”
Section: Managers Are Leadersmentioning
confidence: 99%